1997
DOI: 10.1128/mcb.17.9.5210
|View full text |Cite
|
Sign up to set email alerts
|

Four Distinct Secretory Pathways Serve Protein Secretion, Cell Surface Growth, and Peroxisome Biogenesis in the Yeast Yarrowia lipolytica

Abstract: We have identified and characterized mutants of the yeast Yarrowia lipolytica that are deficient in protein secretion, in the ability to undergo dimorphic transition from the yeast to the mycelial form, and in peroxisome biogenesis. Mutations in the SEC238, SRP54, PEX1, PEX2, PEX6, and PEX9 genes affect protein secretion, prevent the exit of the precursor form of alkaline extracellular protease from the endoplasmic reticulum, and compromise peroxisome biogenesis. The mutants sec238A, srp54KO, pex2KO, pex6KO, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(90 citation statements)
references
References 57 publications
4
86
0
Order By: Relevance
“…However, we cannot rule out that these two mutants contain peroxisomal membrane vesicles, if any, distinct from the presently known peroxisomal reminiscent ghosts but associated with membrane polypeptide(s) not examined in this study. Moreover, given the several recent reports describing possible involvement of ER in peroxisome biogenesis in yeast (53,54), it is plausible that a gene that targets nascent peroxisomal membrane proteins to the ER, rather than peroxisomes, is impaired in ZP119 and ZP165.…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot rule out that these two mutants contain peroxisomal membrane vesicles, if any, distinct from the presently known peroxisomal reminiscent ghosts but associated with membrane polypeptide(s) not examined in this study. Moreover, given the several recent reports describing possible involvement of ER in peroxisome biogenesis in yeast (53,54), it is plausible that a gene that targets nascent peroxisomal membrane proteins to the ER, rather than peroxisomes, is impaired in ZP119 and ZP165.…”
Section: Discussionmentioning
confidence: 99%
“…The SSE1 gene encodes a Pex16p homolog. In the yeast Yarrowia lypolitica, the YlPex16p is required for both peroxisome biogenesis (Eitzen et al, 1997) and mycelial phase specific cell surface protein delivery (Titorenko et al, 1997). The accumulation of small vesicles in the sse1 mutant led to our speculation that SSE1 is involved in storage organelle biogenesis, possibly through affecting protein or membrane trafficking, as does its yeast homolog.…”
mentioning
confidence: 99%
“…The amino-terminal 16 amino acids of the peroxisomal integral membrane protein Pex3p of Hansenula polymorpha were shown to be sufficient to target a reporter protein to the ER (5), whereas treatment of cells of this yeast with brefeldin A led to the accumulation of newly synthesized peroxisomal membrane and matrix proteins at the ER (6). In the yeast Yarrowia lipolytica, the peroxisomal membrane proteins Pex2p and Pex16p were shown to traffic through the ER and to acquire core N-linked glycosylation (7). Findings supporting de novo peroxisome biogenesis in close association with the ER were obtained in cells of Y. lipolytica temperature-sensitive for Pex3p function (8), and studies in the plant Arabidopsis showed that peroxisomal ascorbate peroxidase localized to a subdomain of rough ER that could serve as a compartment for posttranslational sorting to peroxisomes (9).…”
mentioning
confidence: 99%